KOMITMEN ORGANISASI, KEPUASAN KERJA KARYAWAN DAN TURNOVER INTENTION DI PT XYZ - Nandang Suhendar; Linda Mora Siregar; Marhisar Simatupang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
This research was conducted at PT XYZ, this research was conducted based on the phenomenon of high turnover intention in the company, which was 25.9%. Based on research by Widyantara, et al., (2015) showed that there was a negative and significant influence between organizational commitment and job satisfaction on turnover intention. Therefore, this study aims at analyzing the effect of organizational commitment and employee job satisfaction on the turnover intention at PT XYZ. The population in this study amounted to 85 respondents using a total sample where all respondents were sampled. The research method used is quantitative. Based on the results of the multiple regression test of organizational commitment, job satisfaction and turnover intention, there is a negative influence between organizational commitment on turnover intention and the value of Sig. 0.002 < 0.05, secondly there is a negative influence between job satisfaction and turnover intention with the value of Sig. 0.000 <0.05 Third, there is an influence between organizational commitment and job satisfaction on the turnover intention with the value of Sig. 0.000 < 0.05, the value of the coefficient of determination is 23.0%. Therefore, the higher the organizational commitment and job satisfaction of employees, the lower the level of turnover intention will be.